Proceso de atención de enfermería en escolar con eccema dishidrótico. - Macias León, Ronald Miguel (2021)
This clinical case analyzes the condition presented in a schoolboy with dyshidrotic eczema, a condition that develops at the level of the hands and feet, this patient is treated at the pediatrics area of the Alfredo Noboa Montenegro Hospital, in the city of Guaranda. This clinical pathology is frequent, since it occurs annually in 10% of the general population. In the group of skin diseases, it maintains a prevalence of 90%. Dyshidrotic eczema or also called plantar palm has a small explanation since the extremities are fundamental in the daily activities of the human being, therefore, they are in greater contact with chemical elements and irritants unlike other areas of the body. When considered a skin condition with various etiologies, it becomes a disease with a complex diagnosis. To achieve a specific diagnosis, various activities are carried out that together achieve an efficient work, such as an exhaustive and complete anamnesis and physical examination. In this way, the follow-up of this case is based on the application of an adequate nursing care process as specific tools, the use of the clinical history will support the development of the clinical case, the elaboration of the diagnoses and the extension of the interventions. nursing that contributes to the recovery of the integrity of the patient.